Perbandingan Hasil Pemeriksaan Kimia Darah pada Beberapa Tabung Vakum pada Pasien Tuberkulosis Paru - Sakdiah, Siti; Sitanggang, Fardiah Tilawati; Simanjuntak, James P (Universitas Pahlawan Tuanku Tambusai, 2024)
Clinical laboratories are required to produce accurate laboratory examination results so that patient diagnoses are correct. Laboratory examination results are greatly influenced by pre-analytical stages such as the performance of the blood collection tube. Blood collection tubes used in laboratories vary in terms of brand, type and additives in them. Additives in blood collection tubes can affect the accuracy of laboratory test results. To prevent this situation, every laboratory must carry out validation before using blood collection tubes. Almost all clinical laboratories have not carried out collection tube validation activities blood before use. The study aimed to analyze differences in creatinine, GGT, HDL and LDH levels in serum collected in several blood collection tubes used in the laboratory. The research design is analytical descriptive. The sample consisted of 40 healthy adult respondents aged between 18 and 55 years (based on CLSI GP34-A). The parameters studied were creatinine, GGT, HDL and LDH levels from serum collected from blood collection tubes of different types and brands. The research was conducted in the clinical chemistry laboratory, medical laboratory technology department, Health Polytechnic, Ministry of Health, Jambi. in vitro diagnostic technology, namely validation of blood collection tubes. The resulting data from the research was tested using statistical tests.